Changes in the legal notice of the Ministry of Culture: positive and clearer implications for the data of Spanish public libraries and a proposal with greater clarity - Lázaro-Rodríguez, Pedro (Anuario ThinkEPI, 2024)
This paper analyzes the update in April 2024 of the legal notice by the Ministry of Culture of the Government of Spain and its implications for the data and statistics of the Bibliotecas públicas españolas en cifras website. The previous legal notice stated that the license to use the data was limited to the downloading and the private use of the data, with the prohibition of its use (beyond the above), reproduction, distribution, public communication and transformation without the authorization of the Ministry of Culture. This leads to problems for research on public libraries and the reproducibility of studies, especially in the current context of open science. The new legal notice updated in April 2024 is clearer and has positive implications for the reuse of data from the Bibliotecas públicas españolas en cifras website. However, it is argued that it could be improved and written even clearer. A proposal for greater clarity is shared based on the example of the Finnish public library data system as a model of good practice, recommending that the Bibliotecas públicas españolas en cifras website should include a Creative Commons CC BY license and a recommended reference to the data source.